Transfer Between Lifts: Increased Strength in Untrained Exercises. Issue 3 (8th June 2022) - Mang, Zachary; Kravitz, Len; Beam, Jason
ABSTRACT: The principle of specificity confers that physiological adaptations to exercise reflect the specific stimuli applied during an exercise training program. When applied to resistance training (RT), the principle of specificity implies that the acquisition of strength, which is often measured as a 1 repetition maximum, is specific to several variables of an RT program such as intensity, contraction type, and motor pattern. Although the principle of specificity holds true, a phenomenon called "transfer" also occurs when a lifter increases their strength in an exercise that they did not train. For example, if a lifter performed lunges in lieu of back squat, but their back squat strength increased anyway, there would be transfer between the lunge and back squat. This column summarizes recent research that reported transfer between bilateral exercises, unilateral to bilateral exercises, and single-joint to multiple-joint exercises and provides several recommendations for practical applications along the way.